Progression or Resolution of Coxsackievirus B4-Induced Pancreatitis: a Genomic Analysis - Ostrowski, Stephanie E. (American Society for Microbiology, 2004)
Group B coxsackieviruses are associated with chronic inflammatory diseases of the pancreas, heart, and central nervous system. Chronic pancreatitis, which can develop from acute pancreatitis, is considered a premalignant disorder because it is a major risk factor for pancreatic cancer. To explore the genetic events underlying the progression of acute to chronic disease, a comparative analysis of global gene expression during coxsackievirus B4-induced acute and chronic pancreatitis was undertaken. A key feature of acute pancreatitis that resolved was tissue regeneration, which was accompanied by increased expression of genes involved in cell growth, inhibition of apoptosis, and embryogenesis and by increased division of acinar cells. Acute pancreatitis that progressed to chronic pancreatitis was characterized by lack of tissue repair, and the expression map highlighted genes involved in apoptosis, acinoductular metaplasia, remodeling of the extracellular matrix, and fibrosis. Furthermore, immune responses appeared skewed toward development of alternatively activated (M2) macrophages and T helper 2 (Th2) cells during disease that resolved and toward classically activated (M1) macrophages and Th1 cells during disease that progressed. Our hypothesis is that growth and differentiation signals coupled with the M2/Th2 milieu favor acinar cell proliferation, while diminished growth signals and the M1/Th1 milieu favor apoptosis of acinar cells and remodeling/proliferation of the extracellular matrix, resulting in fibrosis.